2020
DOI: 10.1016/j.enpol.2019.111142
|View full text |Cite
|
Sign up to set email alerts
|

The role of competences, engagement, and devices in configuring the impact of prices in energy demand response: Findings from three smart energy pilots with households

Abstract: The paper discusses the dynamics behind price-based incentives in demand response programmes promoting time shifting of energy consumption in households. Through a comparative analysis of smart energy pilots in Norway, Austria, and Denmark, the study shows that economic incentives under certain conditions influence energy-consuming practices of households but not in ways anticipated by widespread rational conceptualisations within economic, engineering, and policy-making approaches. The paper elaborates the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 34 publications
1
28
0
2
Order By: Relevance
“…Thus, the metering scheme makes a difference; however, the qualitative interviews revealed that this should not be understood in a simple rational economic sense. In line with this, recent studies have considered economics in everyday life and have given explanations for how prices may influence practices in ways other than in an economically rational approach [31][32][33][34]. For instance, Strengers argued that price can convey meanings to consumers, for instance, meanings of scarcity or abundance [34].…”
Section: Amount Of and Reasons For Time-shifting And Self-consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the metering scheme makes a difference; however, the qualitative interviews revealed that this should not be understood in a simple rational economic sense. In line with this, recent studies have considered economics in everyday life and have given explanations for how prices may influence practices in ways other than in an economically rational approach [31][32][33][34]. For instance, Strengers argued that price can convey meanings to consumers, for instance, meanings of scarcity or abundance [34].…”
Section: Amount Of and Reasons For Time-shifting And Self-consumptionmentioning
confidence: 99%
“…In our case, the meaning that is conveyed by the price difference is related to questions of self-sufficiency; using one's produced electricity is given meaning through the difference in price between what prosumers can sell electricity for and what prosumers must pay for the electricity they buy. Furthermore, as described in [31,32], the price signal should be viewed in interaction with other elements of everyday practices than just meanings, such as elements of competence and materiality in the form of device interaction, with the role a given price signal has in the performance of practices. Our point is that the interviewed households did not make any calculations before time-shifting; still, the meanings related to the net-metering scheme made many participants time-shift quite often.…”
Section: Amount Of and Reasons For Time-shifting And Self-consumptionmentioning
confidence: 99%
“…Financial benefits made by community institutions or organisations, whether local authorities or non-governmental organisations as a result of implementing DR technologies, can have wider benefits to the community if these are shared through a transparent process. Accordingly, identifying collective economic benefits as well as individual household economic savings [25] are both important considerations.…”
Section: Economic Benefitsmentioning
confidence: 99%
“…From this perspective, the anticipated future has many decentral elements, such as local generation through renewables and local consumption, i.e., security through autarky (Kalkbrenner 2019). By re-integrating energy-related activities into the daily praxis of users (or habits and routines), energy storage can be a driver for users to engage in energy transition, help form new relationships amongst energy actors, and establish new practices (Christensen et al 2020;Kloppenburg et al 2019).…”
Section: A Brief History Of Energy In the Political Economymentioning
confidence: 99%